An afterlife of a scholarly epic: Frazer's Golden Bough and Lewis's argument from myth - Gassman, M (Edinburgh University Press, 2021)
C.S. Lewis believed that Jesus Christ embodied, in historical fact, a mythic pattern of dying and rising exemplified by deities such as Balder and Osiris. Taken from James Frazer's Golden Bough, an enormously influential work of early anthropological scholarship, the idea of a generalized ‘dying and rising’ motif is now substantially outmoded. Resting specifically on the resemblance between that motif and the story of Christ, and not (unlike Tolkien's argument from myth) on the gospel's general qualities as a story, Lewis's argument from myth thus presupposes an incorrect vision of actual ancient pagan religion. That shortcoming is not fatal, however. In contrast to Chesterton in The Everlasting Man (another formative influence), Lewis used an aesthetic or ideal, rather than a historical, conception of myth, which he carefully distinguished from the word's ordinary senses. Although Lewis did believe that ancient myth-makers worshipped ‘dying and rising’ gods, the core of his case is ‘our’ apprehension of a mythic quality in such stories and the Gospels, independent of the beliefs of ancient writers or hearers of myths. That conclusion should discourage overly sanguine appropriations of Lewis's arguments, which never developed into a general theory of mythology and, once the historicity of the ‘dying and rising’ motif is set aside, can be developed into a case much like Tolkien's.